Identifikasi Rhodamin B pada Produk Pangan dan Kosmetik yang Beredar di Bandung - ALIYA NUR HASANAH; IDA MUSFIROH; NYI MEKAR SAPTARINI; DRIYANTI RAHAYU (Fakultas Farmasi Universitas Pancasila, 2014)
Rhodamine B is a colouring agent for paint industry, textile and paper. It causes irritation at respiration systems and has a carcinogenic effect. At high concentration rhodamine B causes liver damages. Nowadays, it has been reported being added into cosmetics and food product such as lipstick, eye shadow, rouge, food paste, and kerupuk. This research was conducted to determine rhodamine B in the products by using HPLC and spectrophotometry UV-Vis. It was done through sample collection, sample preparation, validation of analytical method, and analysis of rhodamine B using HPLC and spectrophotometry UV-Vis. The results of HPLC and spectrophotometry UV-Vis showed that four samples of kerupuk (57,14%) and four samples of food paste (50%) contained rhodamine B. However, rhodamine B was not found in cosmetics. The results showed the urgency of fast methods to identify rhodamine, thus its content in food products is carefully controlled.